Gastroesophageal Reflux Disease—Functional Dyspepsia Overlap: Do Birds of a Feather Flock Together?. (August 2020) - Geeraerts, Annelies; Van Houtte, Brecht; Clevers, Egbert; Geysen, Hannelore; Vanuytsel, Tim; Tack, Jan; Pauwels, Ans
Abstract : INTRODUCTION: Gastroesophageal reflux disease (GERD) and functional dyspepsia (FD) are 2 of the most prevalent upper gastrointestinal (GI) disorders in the Western world. Previous Rome definitions excluded patients with predominant heartburn from the definition of FD because they were considered to have GERD. However, more recent studies showed that heartburn and acid regurgitation are also common symptoms in patients with FD. The aim of this study is to provide an overview of the prevalence of overlap between GERD and FD, the underlying pathophysiology and implications for treatment. METHODS: A review of the literature was performed using the PubMed database, and a meta-analysis with random effects model was completed. RESULTS: This review showed considerable overlap between GERD and FD. A meta-analysis on the data included in this review showed 7.41% (confidence interval [CI]: 4.55%–11.84%) GERD/FD overlap in the general population, 41.15% (CI: 29.46%–53.93%) GERD with FD symptoms, and 31.32% (CI: 19.43%–46.29%) FD with GERD symptoms. Although numerous committees and consensus groups attempted to develop uniform definitions for the diagnosis of GERD and FD, various diagnostic criteria are used across studies and clinical trials (frequency, severity, and location of symptoms). Several studies showed that the overlap between GERD and FD can be explained by a shared pathophysiology, including delayed gastric emptying and disturbed gastric accommodation. DISCUSSION: For diagnoses of GERD and FD, uniform definitions that are easy to implement in population studies, easy to interpret for physicians, and that need to be well explained to patients to avoid overestimation or underestimation of true prevalence are needed. Both GERD and FD coexist more frequently than expected, based on coincidence, suggesting a potential pathophysiological link. More research is needed to explore the common GERD/FD overlap population to identify the underlying pathophysiological mechanisms, which may lead to a more effective therapeutic approach.